Validation of the Personal Impact Health Assessment Questionnaire in Patients with Rheumatoid Arthritis in Kerman, Iran - Mohammad Reza SHAKIBI; Farzaneh ZOLALA; Mahdookht MONSHI; Ali Akbar HGHDOOST (Archives of Rheumatology, 2012)
Objectives: We aimed to generate a valid and adapted version of the Personal Impact Health Assessment Questionnaire (PI HAQ) compatible with Iranian culture. Patients and methods: Between October 2006 and February 2007, data obtained from 100 patients with rheumatoid arthritis (RA) (80 females, 20 males; mean age 51 years; range 20 to 78 years) in a referral rheumatologic clinic in Kerman, Iran were included in this cross-sectional study. The study had five phases; (i) translation and back translation; (ii) cultural adaptation seeking advice of expert rheumatologists in the country; (iii) assessment of face validity by deep interview technique with 20 patients; (iv) assessment of reliability and internal consistency of questionnaire and (v) assessment of content and construct validity using factorial analysis. The results of the PI HAQ were also compared with Short-Form Health Survey (SF-36) and Visual Analog Scale (VAS). Results: The Persian version of the PI HAQ had small changes in three items compatible with Iranian culture in terms of the ability of cutting meat, taking a tub bath and using a toilet. The correlation coefficient in test and re-test was high (r=0.86, p-value <0.001). Cronbach’s alpha was 0.94. The correlation coefficient between the VAS and PI HAQ scores was significantly high (r=0.93, p≤0.001). The factorial analysis showed that the main hidden variable explained over 50% of to total variance (Eigenvalue=50.6%). Conclusion: It seems that the adapted version of the questionnaire is a valid and reliable tool to assess the quality of life of Iranian RA patients.